Early Emotion Knowledge and Later Academic Achievement Among Children of Color in Historically Disinvested Neighborhoods. Issue 6 (31st August 2020) - Ursache, Alexandra; Kiely Gouley, Kathleen; Dawson‐McClure, Spring; Barajas‐Gonzalez, R. Gabriela; Calzada, Esther J.; Goldfeld, Keith S.; Brotman, Laurie M.
Abstract : This study examined longitudinal relations between emotion knowledge (EK) in pre‐kindergarten (pre‐K; M age  = 4.8 years) and math and reading achievement 1 and 3 years later in a sample of 1, 050 primarily Black children (over half from immigrant families) living in historically disinvested neighborhoods. Participants were part of a follow‐up study of a cluster randomized controlled trial. Controlling for pre‐academic skills, other social–emotional skills, sociodemographic characteristics, and school intervention status, higher EK at the end of pre‐K predicted higher math and reading achievement test scores in kindergarten and second grade. Moderation analyses suggest that relations were attenuated among children from immigrant families. Findings suggest the importance of enriching pre‐K programs for children of color with EK‐promotive interventions and strategies.